PENGARUH WORK LIFE BALANCE, STRES KERJA DAN BEBAN KERJA TERHADAP TURNOVER INTENTION - Umi Farida; Titi Rapini; Rizki Listyono Putro (Value : Jurnal Manajemen dan Akuntansi, 2023)
Many workers often change jobs. The purpose of this study is to determine the effect of work life balance, work stress and workload on turnover intention at PT. Daya Surya Sejahtera Ponorogo and Luwes Ponorogo Supermarket and the differences between the two. This study used a simple random sampling method, by taking a sample of 20% of the 273 employee population, so there were 50 samples from PT. Daya Surya Sejahtera Ponorogo and Luwes Ponorogo supermarket. This study uses a quantitative research approach, using the Independent sample t test for data analysis. The analysis technique used is the IBM SPSS 23 software version. The types of data in this study are primary and secondary data. The result was found that the effect of work life balance, work stress and workload had a positive and significant effect on turnover intention among employees of PT. Daya Surya Sejahtera Ponorogo and Luwes Ponorogo Supermarket. The magnitude of the influences of the Luwes Ponorogo Supermarket is greater. It’s hoped that the existing turnover intention problems can be found and get the right solutions in addressing work life balance, work stress and workload. So that it can improve the human resources section in employee management. Keywords: Turnover Intention, Workload